Role of geography in structural transformation: the story of Indian states - Singh, Chhaya (Productivity)
Economic activity as a measure of development is generally estimated in terms of Gross Domestic Product (GDP). But the propriety of GDP as a measure of development has been subject to debate. Different theoretical as well as empirical evidences have hinted towards a relationship between geography and economic growth. This paper attempts to test the geographical proximity hypothesis (i.e., economic growth of a region is determined by its geography in general, and its proximity to other developing or under developed regions in particular) in context of India. This paper argues that the growth rate of a region is determined by the proximity to developed or under-developed states and such clusters of proximate states grow together as a whole. This inference has huge policy implications and makes a favourable case for inclusion of geography as a significant determinant of economic growth. - Reproduced
Keywords: Regions, International trade, Growth models, Geography, Gross Domestic Product--GDP, Costs Economic growth, Production functions, Natural resources, Low income groups, Economic activity, Productivity